Plant-Derived Compounds with Therapeutic Potential for the Treatment of Human Coronavirus Diseases - Adewale, Isaac Olusanjo; Famutimi, Oladoyin Grace; Osiebe, Oghenesivwe (My University, 2024)
Since the advent of modern civilization, few diseases have caused more worldwide socioeconomic disruptions than COVID-19 caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). In some countries, very high proportion of the population have contracted the disease even though it is fatal in only a small percentage of those carrying the virus. In addition to physical measures (social distancing, handwashing, sterilization, etc.), two mainpharmaceutical interventions have been adopted: the development of vaccine/mass vaccination and therapeutic intervention. The recent discovery of SARS-CoV-2 transmission among vaccinated individuals and changes in the genome of the virus arising from mutation leading to new variants (delta, omicron, IHU etc.) suggest the importance of therapeutic intervention targeting different aspects of the molecular mechanisms involved in its virulence. Therapeutic agents targeting essential elements required for viral propagation in the host may also nd application in the management of other viral diseases such as Ebola, Zika, and HIV/AIDS. Targets for drug design include the 16 non-structural proteins, RNA-dependent DNA polymerase, esterase, membrane proteins, spike and envelope proteins, protease and nucleocapsid proteins, and helicase, all present on the virus; host proteases and receptors. Both medicinal plant-derived and synthetic compounds including monoclonal antibodies are now suggested as candidate drugs for COVID-19 and are being developed as suitable therapeutic agents. In this review, some useful information on promising plant-derived therapeutic agents are provided which may be of value in the development of drugs for COVID-19 and other viral diseases. 6/26/24, 6:14 PM Plant-Derived Compounds with Therapeutic Potential for the Treatment of Human Coronavirus Diseases | Proceedings of the National Academy of Sciences, India Section B: Biologic… https://link.springer.com/article/10.1007/s40011-024-01658-5 2/13